One, Two, (Three), Infinity, … : Newspaper and Lab Beauty-Contest Experiments - Bosch-Domènech, Antoni; Montalvo, José G; Nagel, Rosemarie; Satorra, Albert (American Economic Review, 2002)
One, Two, (Three), Infinity, ...: Newspaper and Lab Beauty-Contest Experiments by Antoni Bosch-Domènech, José G. Montalvo, Rosemarie Nagel and Albert Satorra. Published in volume 92, issue 5, pages 1687-1701 of American Economic Review, December 2002